2019
DOI: 10.1104/pp.19.01184
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Metabolism Supports Photosynthesis Start through the Oxidative Pentose Phosphate Pathway in Cyanobacteria

Abstract: Cyanobacteria experience drastic changes in their carbon metabolism under daily light/dark cycles. During the day, the Calvin-Benson cycle fixes CO 2 and diverts excess carbon into glycogen storage. At night, glycogen is degraded to support cellular respiration. The dark/light transition represents a universal environmental stress for cyanobacteria and other photosynthetic lifeforms. Recent studies revealed the essential genetic background necessary for the fitness of cyanobacteria during diurnal growth. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 52 publications
2
56
0
Order By: Relevance
“…We then used dynamic FBA in COMETS with PRO99 medium ( Moore et al, 2007 ) with limited ammonium and diel light conditions to simulate growth over 7 days. The growth curves where qualitatively compared with experimental data from Shinde et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…We then used dynamic FBA in COMETS with PRO99 medium ( Moore et al, 2007 ) with limited ammonium and diel light conditions to simulate growth over 7 days. The growth curves where qualitatively compared with experimental data from Shinde et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient and light limitations are well-known modulators of carbon storage in Prochlorococcus (Zinser et al, 2009; Szul et al, 2019). Recent work has suggested the storage of carbon to be one of the major metabolic tasks during the day-night cycle (Cano et al, 2018; Szul et al, 2019; Shinde et al, 2020). Sampling 10,000 environmental conditions showed that glycogen production decreased at lower light intensities and was less saturated at higher rates (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we explored the ability of our model to dynamically capture biologically relevant phenotypes by performing dynamic FBA simulations of knock-out mutants in Prochlorococcus, focusing on two gene deletions disrupting different parts of glycogen metabolism. Δ glgC breaks synthesis of ADP-glucose and thus the storage of glycogen and Δ gnd , knocking out 6-phosphogluconate dehydrogenase, a key reaction in the Pentose Phosphate pathway found to fuel the Calvin cycle with precursor metabolites during the onset of photosynthesis (Shinde et al, 2020). Our dynamic FBA simulations in COMETS (Figure S5) showed similar growth between Δ gnd and the wild type and slightly lower growth for Δ glgC .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations